Clinical study of carotid superb microvascular imaging in evaluating the activity of Takayasu’s arteritis - Liu, Feng-Ju; Ci, Wei-Ping; Cheng, Yi (Frontiers in Cardiovascular Medicine, 2023)
Objective The goal of this study is to use superb microvascular imaging (SMI) to observe neovascularization in the carotid vessel wall to identify potential Takayasu’s arteritis (TAK) inflammation markers. Methods Bilateral carotid arteries from 96 patients with TAK were imaged by a Doppler ultrasound and SMI. The one-way analysis of variance (ANOVA) was used to document significant differences between the activity and inactivity stages of TAK and the factors closely related to its activity in the binary logistics regression equation. Clinical and laboratory data included age, gender, duration of disease, treatment history, NIH score, erythrocyte sedimentation rate (ESR), and high-sensitivity C-reactive protein. Imaging data included the arterial wall thickness, degree of lesion, SMI grade, and arterial aneurysm formation. Results There were 45 patients in the active TAK stage and 51 in the inactive stage. The one-way ANOVA showed significant differences in SMI (p = 0.001) and ESR (p = 0.022) between the active and inactive groups. The binary logistics regression analysis showed that SMI was an independent risk factor for TAK activity (B = −1.505, S.E = 0.340, Wald = 19.528, OR = 0.222 95%, CI = 0.114–0.433, p < 0.01). Using SMI G1 or G2 as the cutoff values for the diagnosis of active TAK, the positive predictive value, sensitivity, and specificity were 60 and 86%, 84% and 56%, and 54% and 92%, respectively. Conclusion The SMI grade is a potential marker of disease activity in patients with TAK.